2017
DOI: 10.4012/dmj.2016-192
|View full text |Cite
|
Sign up to set email alerts
|

Bonding durability between acrylic resin adhesives and titanium with surface preparations

Abstract: The purpose of the present study was to evaluate the efficacy of pretreatment on the bonding durability between titanium casting and two acrylic adhesives. Cast titanium disk specimens treated with four polymer-metal bonding systems as follow: 1) air-abraded with 50-70 μm alumina, 2) 1)+Alloy Primer, 3) 1)+M.L. Primer and 4) tribochemical silica/silane coating system (Rocatec System). The specimens were bonded with M bond or Super-bond C&B adhesive. The shear bond strengths were determined before and after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
5
11
0
Order By: Relevance
“…Similarly, in a study conducted by Maruo et al [45], the processes of plasma beam application and sandblasting with Al 2 O 3 produce weaker results than the metal primer application with regard to the bond between the acrylic resin and the cobalt-chrome alloy. Several studies demonstrated that the only mechanical methods used in some studies were insufficient and that the application of chemical agents, such as silane and metal primers, was effective in enhancing the bond, which is supportive of our study [2, 3, 8, 9, 32, 33].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Similarly, in a study conducted by Maruo et al [45], the processes of plasma beam application and sandblasting with Al 2 O 3 produce weaker results than the metal primer application with regard to the bond between the acrylic resin and the cobalt-chrome alloy. Several studies demonstrated that the only mechanical methods used in some studies were insufficient and that the application of chemical agents, such as silane and metal primers, was effective in enhancing the bond, which is supportive of our study [2, 3, 8, 9, 32, 33].…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, various mechanical and chemical methods have been employed to enhance the adhesive bonding of acrylic resins to metal alloys. Electrolytic etching, chemical etching, silica coating, spark erosion, laser application, sandblasting with Al 2 O 3 , and the application of metal primers are the most commonly used methods developed for this purpose [2, 3, 612].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that air-abrasion of silica-coated alumina particles (Rocatec system) can chemically modify material surfaces, leading to improve bonding properties [37][38][39][40] . Alumina air-abrasion has been considered to have a mechanical effect on adhesive bonding, but the chemical effects have not been clarified so far.…”
Section: Discussionmentioning
confidence: 99%